Geological and geophysical features of and controls on occurrence and accumulation of gas hydrates in the first offshore gas-hydrate production test region in the Shenhu area, Northern South China Sea - Zhang, Wei; Liang, Jinqiang; Wei, Jiangong; Lu, Jing'an; Su, Pibo; Lin, Lin; Huang, Wei; Guo, Yiqun; Deng, Wei; Yang, Xiaolu; Wan, Zhifeng (Marine and petroleum geology, 2020)
Integrated three-dimensional seismic, logging, sediment cores, and geochemical testing data were collected from Guangzhou Marine Geological Survey 3 and 4 hydrate drilling expeditions and used in this study for a comprehensive investigation of the geological and geophysical features and accumulation mechanism of hydrates in the first offshore gas-hydrate production test region (GHPTR) in the Shenhu area of the South China Sea. Seismic signatures indicative of disseminated hydrates and free gas include the bottom simulating reflector (BSR), gas chimney, and mud diapir associated with enhanced seismic reflections, acoustic blanking, masking, and chaotic appearance have been observed. The acoustic travel-time responses, density, and compensated neutron three porosity log analysis, high-precision grid tomography inversion analysis, and constrained sparse spike inversion confirm the presence of free gas below the gas-hydrate-bearing zone (GHBZ). Free-gas-bearing zones have significantly different p-wave impedances and low-velocity anomalies than the overlying GHBZ and surrounding strata. These anomalous zones are controlled by the structural attitude of the reservoir strata, which are characterized as inter-bedded stratigraphic units. Variations in the type and geological characteristics of the hydrocarbon migration pathways were observed between sites W18 and W19 on the western ridge and sites W11 and W17 on the eastern ridge in the GMGS study area. The efficiency of gas migration in the western ridge may be higher than that in the eastern ridge, resulting in variations in hydrate gas types, thickness of the GHBZ, and gas migration flux and accumulation. Except for site W11, hydrates were recovered below the structure I inferred BSR at sites W17, W18, and W19. The gas-hydrate stability zone calculations reveal that the structure I hydrate stability zone differs from the BSR depth and is generally shallower than the base of the logging anomaly, indicating the coexistence of structure I and II hydrates. The BSR is not indicative of the BGHSZ; it is rather regarded as a transitional indicator of structure I and II gas hydrates in the GHPTR. The appearance of free gas and hydrates below the structure I inferred BSR indicates that the Shenhu area is characterized by a complex hydrate formation and accumulation system resulting from the supply of biogenic and thermogenic gases. Despite fine-grained host sediments predominating the GHPTR, the coupling of favorable conditions including efficient hydrocarbon generation, sufficient gas supply, multiple pathways for gas migration, and relatively high reservoir porosity have led to the development of highly saturated gas-hydrate accumulations within relatively thick sedimentary sections, which demonstrates a significant resource potential. [Display omitted] •Gas hydrate petroleum system of the China first offshore hydrate production test region is investigated.•Gas hydrate and underlying free gas are evaluated based on velocity and acoustic impedance inversion.•The BSR represents a transitional indicator of structure I and structure II gas hydrate.•Presence of foraminifera is not a prerequisite for the emergence of high-saturation hydrates.